Pembinaan Mantan Tunasusila di Panti Sosial Karya Wanita (PSKW) Mulya Jaya Pasar Rebo Jakarta Timur - Setyo Sumarno (Jurnal Penelitian Kesejahteraan Sosial, 2013)
The Karya Wanita Mulya Jaya Institution is a social institution overlooking ex prostitutes. In their service, they go through several phases, from initial approach to termination. After care service is one of phases done after a client back in his or her community. This research is done to know the implementation of an aftercare service in this social institution. The research approach used is qualitative-descriptive technique, aiming to describe the rehabilitation service process, especially in aftercare phase. The research finds that an aftercare service is interpreted as a monitoring and evaluation, not all clients living in their community receiving an aftercare service. The aftercare service is implemented after 2-3 months clients receiving service in the institution, together with Rp 800.000,- giving stimulant to each client. The service given by the institution is very worthwhile for the clients and their families to enhance to a better lives and adaptation among their community.